2020
DOI: 10.3390/cancers12123608
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Dabrafenib Plus Trametinib Combination in Patients with BRAF V600E-Mutant NSCLC in Real-World Setting: GFPC 01-2019

Abstract: Dabrafenib plus trametinib combination is approved in Europe for BRAF V600E-mutant metastatic non-small-cell lung cancer (NSCLC). The objective of this study was to assess efficacy and safety of this combination in a real-world setting. This retrospective multicentric study included 40 patients with advanced NSCLC harboring BRAF V600E mutation and receiving dabrafenib plus trametinib. The median progression-free survival (PFS) and overall survival (OS) were 17.5 (95% CI 7.1–23.0) months and 25.5 (95% CI 16.6–n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Following treatment with dabrafenib plus trametinib, mPFS of 10.9 months was recorded in patients with previously untreated BRAF V600E mutant NSCLC 11 . Another retrospective multicentric study reported mPFS of 17.5 months in 40 BRAF V600E‐positive advanced NSCLC patients treated with dabrafenib plus trametinib 23 . Horn and colleagues demonstrated the efficacy of BRAFi/MEKi regimens as a later line of treatment in 20 BRAF V600E NSCLC patients and longer OS from metastatic onset relative to patients receiving usual care, highlighting the importance of targeted therapy in BRAF V600 mutant NSCLC cases 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following treatment with dabrafenib plus trametinib, mPFS of 10.9 months was recorded in patients with previously untreated BRAF V600E mutant NSCLC 11 . Another retrospective multicentric study reported mPFS of 17.5 months in 40 BRAF V600E‐positive advanced NSCLC patients treated with dabrafenib plus trametinib 23 . Horn and colleagues demonstrated the efficacy of BRAFi/MEKi regimens as a later line of treatment in 20 BRAF V600E NSCLC patients and longer OS from metastatic onset relative to patients receiving usual care, highlighting the importance of targeted therapy in BRAF V600 mutant NSCLC cases 24 .…”
Section: Discussionmentioning
confidence: 99%
“…11 Another retrospective multicentric study reported mPFS of 17.5 months in 40 BRAF V600E-positive advanced NSCLC patients treated with dabrafenib plus trametinib. 23 Horn and colleagues demonstrated the efficacy of BRAFi/MEKi regimens as a later line of treatment in 20 BRAF V600E NSCLC patients and longer OS from metastatic onset relative to patients receiving usual care, highlighting the importance of targeted therapy in BRAF V600 mutant NSCLC cases. 24 In our study, mPFS in 13 patients receiving BRAF-TKIs was 7.0 months for all treatment lines.…”
Section: Survival Of Patients With Primary Braf Mutationsmentioning
confidence: 99%
“…19 The panel deleted single-agent dabrafenib as a treatment option for patients with BRAF V600E mutation-positive metastatic NSCLC who cannot tolerate combination therapy with dabrafenib 1 trametinib; single-agent vemurafenib remains an option in this setting. 37,38 Although less toxic, dabrafenib monotherapy is less effective than combination therapy with dabrafenib 1 trametinib. 39 For the 2020 updates, the panel added selpercatinib and pralsetinib as preferred first-line therapy options for patients with RET rearrangement-positive metastatic NSCLC.…”
Section: Molecular Biomarkersmentioning
confidence: 99%
“…Among the nine patients receiving first-line therapy, median PFS and OS were 16.8 (95% CI: 6.1–23.2) and 21.8 months (95% CI: 1.0–not achieved), respectively. Median PFS and OS were 16.8 months (95% CI: 6.1–23.2) and 25.5 months (95% CI: 16.6 months–not met), respectively, in 31 patients receiving second-line therapy or above ( 22 ). In our study, 23.5% (12/51) and 39.1% (9/23) of the patients received BRAF/MEK-targeted therapy as first- and second-line therapies, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, a real-world study assessed the efficacy of combined dabrafenib and trametinib in treating BRAF V600E mutated advanced NSCLC. Across the entire cohort, median PFS and OS were 17.5 months (95% confidence interval [CI] 7.1–23.0 months) and 25.5 months (95% CI 16.6–not reached), respectively ( 22 ). Another study reported that the OS in BRAF-targeted therapy was longer (56.5 months) than that of conventionally treated patients (27.2 months), further emphasizing the importance of targeting treatments for BRAF V600E mutated NSCLC ( 23 ).…”
Section: Introductionmentioning
confidence: 99%